Wire cutting as a viable substitute for machining standardized V-notches for Charpy specimens - Cantero, Mariano; Lorusso, Hernán; Simoncelli, Alejandro; Migliorino, Diego; Martínez Krahmer, Daniel; Sánchez Egea, Antonio J.; Spanu, Florencia (Springer, 2025)
In engineering, selecting the right material is crucial, with toughness being a key property. The Charpy impact test is essential for assessing a material’s ability to absorb energy during sudden loads, aiding in material selection, temperature behavior analysis, and heat treatment effects. Modern manufacturing technologies address materials with poor machinability, such as those in metalworking. Fabricating standardized Charpy specimens requires machining notches. While traditional milling methods are standard, there is growing interest in alternative processes like electro-discharge machining, which can replace milling without significantly affecting mechanical properties. This study evaluates the feasibility of wire electrical discharge machining with a conventional wire as an alternative to the standardized machining method for creating notches in Charpy specimens. The results show that for brass and AISI 1045 steel, no significant differences in resilience were observed between processes. However, the resilience of the aluminum specimens tested by Charpy with the WEDM notch was 28% lower than that of the machined specimens. This work demonstrates the potential of wire electrical discharge machining for manufacturing V-notches in Charpy specimens across a broad range of materials while preserving the sensitivity of the standard test. These findings highlight valuable insights for its application in various industries where impact toughness assessment is critical.
Keywords: Ingeniería y tecnología::Ingeniería de materiales; Ciencia de los materiales; Tecnología mecánica; Metalurgia